Penguatan Manajemen Aset Tetap dan Akademik Sekolah untuk Meningkatkan Kinerja Layanan Pendidikan - Rahayu, Sri; Jumaili, Salman; Rahayu, Rahayu; Saudagar, Ferdiaz; Utomo, Pradita Eko Prasetyo (Jurnal JUPEMA, 2024)
Schools have a responsibility to provide education for the nation's generation well. Schools need good fixed assets to be able to provide optimal academic services for students. The Jambi University community service activities team carries out activities to strengthen the administration of the school's fixed assets and academics. Activities are carried out through the Kukerta MBKM DLT scheme with a location at State Elementary School 03, Olak Kemang Village, Danau Teluk District, Jambi City. This activity was carried out by lecturers and students from three study programs, namely Accounting, Educational Administration and Information Systems. Community service activities (PPM) are carried out in the form of assistance in managing fixed assets and education administration. Students together with the school carry out the process of inventorying and structuring the administration of fixed assets and the school reading room. The school was very enthusiastic about participating in this activity. This is evident from the discussion process, contributions and participation of all parties in the school in supporting this activity. The school really hopes that other mentoring and training activities related to increasing skills for teachers and staff in managing the administration of educational institutions can be carried out in the future. The school also hopes that the collaboration between Jambi University and the School will continue with other activities that can be developed further. Abstrak. Sekolah memiliki tanggung jawab untuk menyelenggarakan pendidikan bagi generasi bangsa dengan baik. Sekolah membutuhkan aset tetap yang baik untuk dapat memberikan layanan akademik secara optimal bagi siswa. Tim kegiatan pengabdian kepada masyarakt Universitas Jambi melakukan kegiatan penguatan administrasi aset tetap dan akademik sekolah. Kegiatan dilakukan melalui skema Kukerta MBKM DLT dengan Lokasi di Sekolah Dasar Negeri 03 Kelurahan Olak Kemang Kecamatan Danau Teluk Kota Jambi. Kegiatan ini dilakukan oleh dosen dan mahasiswa dari tiga program studi yaitu Akuntansi, Administrasi Pendidikan dan Sistem Informasi. Kegiatan pengabdian kepada masyarakat (PPM) dilakukan dalam bentuk pendampingan pengeloaan aset tetap dan administrasi pendidikan. Mahasiswa bersama pihak sekolah melakukan proses inventarisasi dan penataan administrasi aset tetap dan ruang baca sekolah. Pihak sekolah sangat antusias mengikuti kegiatan ini. Hal ini terbukti dari proses diskusi, kontribusi dan partisipasi seluruh pihak di sekolah dalam mendukung kegiatan ini. Sekolah sangat berharap kegiatan pendampingan dan pelatihan lain terkait peningkatan keterampilan bagi guru dan pegawai dalam mengelola administrasi institusi pendidikan dapat dilakukan pada masa yang akan datang. Sekolah juga berharap Kerjasama antara Universitas Jambi dan Sekolah terus berlanjut dengan kegiatan lain yang dapat dikembangkan lebih lanjut.